Tek taraflı Crowe Tip 3 ve Crowe Tip 4 kalça displazisi olan hastalarda total kalça artroplastisi sonrası alt ekstremite ve omurgada oluşan değişikliklerin klinik ve radyolojik sonuçları Clinical and radiological outcomes of changes in the lower extremity and spine following total hip arthroplasty in patients with unilateral Crowe Type III and Crowe Type IV hip dysplasia - KAYA , HAKAN BATUHAN (My University, 2025)
Amaç: Tek taraflı Crowe tip 3 ve Crowe tip 4 kalça displazisi olan hastalarda total kalça artroplastisi sonrası kısa dönem alt ekstremite ve omurgada oluşan değişikliklerin klinik ve radyolojik sonuçlarını göstermek. Gereç ve yöntem: Bezmialem Vakıf Üniversitesi Tıp Fakültesi Ortopedi ve Travmatoloji Anabilim Dalı tarafınca Crowe sınıflandırılmasına göre Tip 3 ve Tip 4 kalça displazisi olan hastalar prospektif olarak değerlendirildi. Çalışma öncesi Clinical Trials'a çalışma kaydı yapılmıştır. Hastaların demografik ve ameliyat özelliklerine ek olarak preoperatif ve postoperatif 1. yılda ayakta ön-arka pelvis grafi, ön-arka bacak uzunluk grafisi, ayakta ve oturarak lumbosakral ön- arka ve lateral grafisi istendi. Harris kalça skoru(HHS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Kısa form 12(SF-12) yaşam kalitesi ölçeği, Kujala patellofemoral ağrı Skoru, Oxford diz skoru, Oswestry Bel ağrısı Engellilik anketi(ODI), Roland Morris engellilik anketi, American Orthopedic Foot-and-Ankle Society Ankle-Hindfoot Score(AOFAS), Ayak ve ayak bileği engellilik indeksi (FADI) Skorları alınıp değerlendirildi. Bulgular: Çalışmaya yaş ortalaması 52,70±11,83 olan 33 hasta dahil edildi. Ortalama takip süresi 18,27±7,04 aydır. 13 (%39,3) hastanın Crowe tip 3 ve 20(%60,6) hastanın Crowe tip 4 kalçası vardı. HHS ipsilateral taraf (p<0,001), WOMAC ipsilateral taraf (p<0,001), HHS kontralateral taraf (p:0,001), WOMAC kalça kontralateral taraf (p:0,003), SF-12 skorları(p<0,001), ODI (p:0,014), Roland Morris engellilik anketi (p:0,004) ve WOMAC diz ipsilateral taraf (p:0,038) skorlarında postoperatif anlamlı bir iyileşme gösterildi. Radyolojik ölçümlerde ameliyat sonrası MAD ipsilateral taraf anlamlı olarak azaldı(p<0,001), uzunluk farkı anlamlı olarak azaldı (p<0,001), JLCA ipsilateral taraf anlamlı olarak arttı(p:0,024), AJLO ipsilateral taraf anlamlı olarak arttı(p:0,049), SS anlamlı olarak arttı(p:0,027) ve LLA anlamlı olarak azaldı(p<0,001). Sonuç: Vakalarımızın kısa dönem sonuçlarında literatürle uyumlu şekilde alt ekstremite dizilimi opere edilen tarafta ameliyat öncesi valgus dizilimi karşı tarafta varus dizilimi hakimken, opere edilen tarafta ameliyat sonrası valgusun azaldığı ancak nötre gelmediği karşı tarafta varus diziliminin değişmediği gösterildi. Spinopelvik parametrelere baktığımızda SS preoperatif ve postoperatif normal sınırlar içinde bulunmuş ve istatiksel olarak postoperatif anlamlı artış gösterilmiştir. LLA ise preoperatif ve postoperatif normal sınırlar içinde olsa da postoperatif istatiksel olarak anlamlı olarak düşük bulunmuştur. Aynı zamanda bakılan kalça skorları, SF-12, lomber skorlar ve WOMAC ipsilateral diz skorunda postoperatif anlamlı iyileşme gösterildi. Anahtar kelimeler: erişkin kalça displazisi, crowe tip 3, crowe tip 4, total kalça artroplastisi, subtrokanterik femur kısaltma osteotomisi
Objective: To demonstrate the clinical and radiological outcomes of changes in the lower extremities and spine in patients with unilateral Crowe type 3 and type 4 hip dysplasia following total hip arthroplasty in the short term. Materials and Methods: Patients with Crowe type 3 and type 4 hip dysplasia were prospectively evaluated in the Department of Orthopedics and Traumatology at Bezmialem Vakıf University Faculty of Medicine. The study was registered in ClinicalTrials prior to its commencement. In addition to demographic and surgical characteristics, preoperative and postoperative assessments at the 1-year follow-up included standing anteroposterior pelvis radiographs, standing anteroposterior leg length radiographs, and standing and sitting anteroposterior and lateral lumbosacral radiographs. Harris Hip Score (HHS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Short Form 12 (SF-12) Quality of Life Scale, Kujala Patellofemoral Pain Score, Oxford Knee Score, Oswestry Disability Index (ODI), Roland Morris Disability Questionnaire, American Orthopedic Foot-and-Ankle Society Ankle-Hindfoot Score (AOFAS), and Foot and Ankle Disability Index (FADI) scores were all collected and evaluated. Results: A total of 33 patients with a mean age of 52.70±11.83 years were included in the study. The average follow-up period was 18.27±7.04 months. Among these, 13 patients (39.3%) had Crowe type 3 and 20 patients (60.6%) had Crowe type 4 hip dysplasia. Significant postoperative improvements were observed in HHS (ipsilateral side, p<0.001), WOMAC (ipsilateral side, p<0.001), HHS (contralateral side, p=0.001), WOMAC (contralateral side, p=0.003), SF-12 scores (p<0.001), ODI (p=0.014), Roland Morris Disability Questionnaire (p=0.004), and WOMAC knee score (ipsilateral side, p=0.038). Radiological measurements showed a significant reduction in the Mean Acetabular Deformity (MAD) on the ipsilateral side (p<0.001), a significant reduction in leg length discrepancy (p<0.001), a significant increase in the Joint Line Congruency Angle (JLCA) on the ipsilateral side (p=0.024), a significant increase in the Acetabular Joint Line Orientation (AJLO) on the ipsilateral side (p=0.049), a significant increase in Sacral Slope (SS) (p=0.027), and a significant reduction in Lumbosacral Lordosis Angle (LLA) (p<0.001) on the ipsilateral side. Conclusion: In the short-term results of our cases, consistent with the literature, the alignment of the lower extremities showed that preoperatively, the operated side had a valgus alignment of the knee and the contralateral side had varus alignment. Postoperatively, valgus alignment on the operated side decreased but did not return to neutral, while varus alignment on the contralateral side remained unchanged. When assessing spinopelvic parameters, Sacral Slope (SS) remained within normal preoperative and postoperative limits and showed a statistically significant increase. Lumbosacral Lordosis Angle (LLA) remained within normal limits preoperatively and postoperatively, but was statistically significantly lower postoperatively. Furthermore, significant postoperative improvement was observed in hip scores, SF-12, lumbar scores, and WOMAC knee score on the ipsilateral side. Keywords: adult hip dysplasia, Crowe type 3, Crowe type 4, total hip arthroplasty, subtrochanteric femoral shortening osteotomy
Keywords: Ortopedi ve Travmatoloji = Orthopedics and Traumatology